Portrayal and management of a rarely seen alveolar bone resorption pattern mimicking the Combination Syndrome: a clinical report - Alper Uyar; Bulent Piskin; Cumhur Sipahi; Faruk Emir; İsmail Avsever; Simel Ayyıldız (Cumhuriyet University, 2014)
Treatment of severely resorbed edentulous alveolar ridges is still a challenging topic of prosthodontics. Combination Syndrome is one of the most remarkable intraoral manifestations of excessive alveolar bone resorption which may be observed at the denture wearing patients with complete edentulous maxilla and bilateral partial edentulous mandibula. Since its first recognition in 1972, the major symptoms and morphological features of the Combination Syndrome such as enlarged maxillary tuberosities and resorbed edentulous ridges were often portrayed as being bilaterally located in either sides of the midsagittal plane. The aim of the present study was to describe a rarely seen alveolar bone resorption pattern mimicking the Combination Syndrome and to report the prosthetic treatment approach applied for its rehabilitation.